Structure-function models of temporal, spatial, and spectral characteristics of non-invasive whole brain functional imaging - Raj, Ashish; Verma, Parul; Nagarajan, Srikantan (Frontiers in Neuroscience, 2022)
We review recent advances in using mathematical models of the relationship between the brain structure and function that capture features of brain dynamics. We argue the need for models that can jointly capture temporal, spatial, and spectral features of brain functional activity. We present recent work on spectral graph theory based models that can accurately capture spectral as well as spatial patterns across multiple frequencies in MEG reconstructions.